Clinical Actionability of Multigene Panel Testing for Hereditary Breast and Ovarian Cancer Risk Assessment - Andrea Desmond; Allison W. Kurian; Michele Gabree; Meredith Mills; Michael J. Anderson; Yuya Kobayashi; Nora Horick; Shan Yang; Kristen M. Shannon; Nadine Tung; James M. Ford; Stephen E. Lincoln; et al. (2015)
IMPORTANCEThe practice of genetic testing for hereditary breast and/or ovarian cancer (HBOC) is rapidly evolving owing to the recent introduction of multigene panels.While these tests may identify 40% to 50% more individuals with hereditary cancer gene mutations than does testing for BRCA1/2 alone, whether finding such mutations will alter clinical management is unknown.OBJECTIVE To define the potential clinical effect of multigene panel testing for HBOC in a clinically representative cohort. DESIGN, SETTING, AND PARTICIPANTSObservational study of patients seen between 2001 and 2014 in 3 large academic medical centers.We prospectively enrolled 1046 individuals who were appropriate candidates for HBOC evaluation and who lacked BRCA1/2 mutations. INTERVENTIONSWe carried out multigene panel testing on all participants, then determined the clinical actionability, if any, of finding non-BRCA1/2 mutations in these and additional comparable individuals. MAIN OUTCOMES AND MEASURESWe evaluated the likelihood of (1) a posttest management change and (2) an indication for additional familial testing, considering gene-specific consensus management guidelines, gene-associated cancer risks, and personal and family history.RESULTS Among 1046 study participants, 40 BRCA1/2-negative patients (3.8%; 95% CI, 2.8%-5.2%)harbored deleterious mutations, most commonly in moderate-risk breast and ovarian cancer genes (CHEK2, ATM, and PALB2) and Lynch syndrome genes.Among these and an additional 23 mutation-positive individuals enrolled from our clinics, most of the mutations (92%) were consistent with the spectrum of cancer(s) observed in the patient or family, suggesting that these results are clinically significant.Among all 63 mutation-positive patients, additional disease-specific screening and/or prevention measures beyond those based on personal and family history alone would be considered for most (33 [52%] of 63; 95% CI, 40.3%-64.2%).Furthermore, additional familial testing would be considered for those with first-degree relatives (42 [72%] of 58; 95% CI, 59.8%-82.2%)based on potential management changes for mutation-positive relatives.This clinical effect was not restricted to a few of the tested genes because most identified genes could change clinical management for some patients. CONCLUSIONS AND RELEVANCEIn a clinically representative cohort, multigene panel testing for HBOC risk assessment yielded findings likely to change clinical management for substantially more patients than does BRCA1/2 testing alone.Multigene testing in this setting is likely to alter near-term cancer risk assessment and management recommendations for mutation-affected individuals across a broad spectrum of cancer predisposition genes.